2020
DOI: 10.20452/pamw.15625
|View full text |Cite
|
Sign up to set email alerts
|

Thromboinflammatory state and venous thromboembolic events in patients with coronavirus disease 2019 admitted to a non-intensive care ward: a prospective study

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In the acute phase of COVID-19, the presence of a thromboinflammatory state, characterized by high levels of inflammatory parameters, such as CRP, ferritin and Interleukin-6, and some coagulation indices, such as fibrinogen and D-dimer, has been described [ 27 , 28 ]. These changes were associated with a high frequency of venous thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute phase of COVID-19, the presence of a thromboinflammatory state, characterized by high levels of inflammatory parameters, such as CRP, ferritin and Interleukin-6, and some coagulation indices, such as fibrinogen and D-dimer, has been described [ 27 , 28 ]. These changes were associated with a high frequency of venous thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the documentation of coagulopathy, an increased incidence of venous thromboembolism (VTE) has been reported in patients hospitalized for COVID-19 pneumonia with respect to "usual" infectious respiratory disease. Actually, the incidence of VTE in non-ICU patients admitted for infectious respiratory disease is estimated around 5%, with adequate thromboprophylaxis, while the incidence in COVID-19 patients has been reported as high as 20% [4][5][6][7][8][9][10][11]. In the SARS-CoV-2 pandemic scenario, the most reliable data derive from studies carried out in ICU patients, while less robust information is available for patients with COVID-19 pneumonia admitted to non-ICU settings, such as those of Pneumology and Internal Medicine Units (IMUs).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a high incidence of venous thromboembolism (VTE) has been reported in patients hospitalized for COVID-19 pneumonia. Indeed, the incidence of VTE in patients hospitalized for COVID-19 pneumonia in a non-ICU setting has been reported up to 20% [3][4][5][6][7][8]. In a recent large multicenter prospective study in non-ICU patients with moderate-severe COVID-19, we reported an incidence of deep vein thrombosis (DVT) of the lower limbs, using serial compression ultrasound (CUS) surveillance of 13.7% [9] during the first Italian wave of pandemic.…”
Section: Introductionmentioning
confidence: 99%